2019
DOI: 10.1097/tp.0000000000002425
|View full text |Cite
|
Sign up to set email alerts
|

Open Randomized Multicenter Study to Evaluate Safety and Efficacy of Low Molecular Weight Sulfated Dextran in Islet Transplantation

Abstract: Original Clinical Science-General Background. When transplanted human pancreatic islets are exposed to blood during intraportal infusion, an innate immune response is triggered. This instant blood-mediated inflammatory reaction (IBMIR) activates the coagulation and complement cascades and leads to the destruction of 25% of all transplanted islets within minutes, contributing to the need, in most patients, for islets from more than 1 donor. Low molecular dextran sulfate (LMW-DS) has been shown in experimental s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…The release and activation of multiple growth factors from peripheral and central tissues would initiate a program of diverse downstream cellular responses relating to metabolism, tissue repair, and regeneration. For example, ILB ® induces release of Hepatocyte Growth Factor (HGF) from sequestered stores [35,68], a growth factor known to be neuroprotective and to stimulate glucose transport, metabolism and oxidative stress [69,70].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The release and activation of multiple growth factors from peripheral and central tissues would initiate a program of diverse downstream cellular responses relating to metabolism, tissue repair, and regeneration. For example, ILB ® induces release of Hepatocyte Growth Factor (HGF) from sequestered stores [35,68], a growth factor known to be neuroprotective and to stimulate glucose transport, metabolism and oxidative stress [69,70].…”
Section: Discussionmentioning
confidence: 99%
“…While high molecular weight dextran sulfate possesses toxic effects, inducing cancer development and inflammation [31][32][33], ILB ® is a proven safe and well-tolerated LMW-DS. Previous studies showed that LMW-DS dose-dependently limits the instant blood-mediated inflammatory reaction (IBMIR) [34,35], inhibits E-selectin-mediated adhesion of neutrophils to endothelial cells [36,37], prevents adherence of peritoneal metastases [38], and improves the effectiveness of therapy and reduces mortality in patients with acute cerebral infarction treated with the thrombolytic agent urokinase [39]. Of particular mechanistic relevance to TBI, subcutaneous injection of ILB ® induces a rapid release of pharmacologically relevant levels of Hepatocyte Growth Factor (HGF) into the circulation in laboratory animals and healthy human volunteers, which may provide a neurotrophic stimulus to the injured central nervous system (CNS) [35].…”
Section: Introductionmentioning
confidence: 99%
“…Low molecular weight dextran sulfate (LMW-DS, MM 5000) is an alternative inhibitor of IBMIR [80,81,82,83,84]. An open randomized multicenter study showed that LMW-DS has a similar efficacy in inhibiting IBMIR to promote islet engraftment when compared with heparin [84]. Activated protein C (APC) is another potent inhibitor which exerts anticoagulant, anti-inflammatory, and antiapoptotic activities by acting directly on cells.…”
Section: Islet Transplantationmentioning
confidence: 99%
“…After transplantation, beta cell survival can be impaired by acute and/or chronic factors. Immediately when islets are injected, direct contact with the vascular system exposes them to an instant blood-mediated reaction (IBMIR) which contributes to early graft loss 15 17 . In addition, there is a substantial risk of beta cell death due to acute hypoxia.…”
Section: Challenges With the Intrahepatic Site For Clinical Transplanmentioning
confidence: 99%